COMPARATIVE ANALYSIS OF THE LEVEL OF TAXATION IN ROMANIA AND EUROPEAN UNION - MARIA ZENOVIA GRIGORE; MARIANA GURAU (Challenges of the Knowledge Society)
This paper contains a statistical and economic analysis of the tax system of Romania in the last decade, as well as comparisons with the other states of the European Union. The overall tax ratio of Romania, i.e. the sum of taxes and social security contributions in the Gross Domestic Product (GDP), is the lowest in the European Union. Considering the fact that the GDP value, that constitutes the denominator of the overall tax ratio, includes estimates of production by the informal sector (the “grey” and “black” economy), this reduction can be explained not only by tax reductions, but also by the high tax evasion.